Cash social assistance Covid-19, welfare, and economic performance in Indonesia - Hermawan, Iwan; Widyarini, Maria (Jurnal Ekonomi dan Bisnis, 2023)
The Cash Social Assistance Covid-19 (BST Covid-19) aims to help the community affected by the Covid-19 pandemic. However, the assistance index (the social assistance amount per household), which is relatively small and has a uniform magnitude, is "considered" not yet accommodating to the various economic burdens of the community, especially in urban areas. The BST-19 has also become vague in maintaining purchasing power. This study tries to analyze the BST Covid-19 impact on the household's welfare in urban and rural regions, and, at the same time, relate it to Indonesia's economic performance. This study uses a quantitative approach to the Computable General Equilibrium Model (CGE). Secondary data is needed to support the construction of the model. The data come from Central Bureau Statistics, the Ministry of Social Affairs, the Ministry of Finance, previous research results, etc. The study results show that the provision of Covid-19 BST positively impacts household welfare even though it has not been reflected at the macroeconomic level. Differentiation of the BST Covid-19 index considers the economic burden in which the household lives will potentially increase assistance benefits. The provision of BST Covid-19 combined with community empowerment programs or policies has proven to have better benefits than only being provided with social assistance.